Personnel Policy Of The Mari Militia in the 60th - 90th of the XX Century: Problems of Continuity - V. A. Ivanov; I. A. Boyarintseva (Сибирское юридическое обозрение, 2015)
The article analyses the status and problems of continuity in the personnel policy of the Ministry of Internal Affairs of the Mari ASSR from 1961 to 1991. The authors examine the basic forms and methods of ensuring the continuity of militia personnel and underline the obvious achievements and drawbacks made in this work.